Transcutaneous electrical acupoint stimulation for upper limb motor recovery after stroke: a systematic review and meta-analysis - Xiaoyu Wang; Xiaoyu Wang; Xiaoyu Wang; Lianjun Yin; Yikun Wang; Yikun Wang; Haining Zhang; Haining Zhang; Shiying Zhang; Shiying Zhang; Jiantong Wu; Jiantong Wu; et al. (Frontiers in Aging Neuroscience)
BackgroundTranscutaneous electrical acupoint stimulation (TEAS) is an innovative, non-invasive therapy that stimulates the contraction of paralyzed muscles in the upper limbs, promoting functional recovery. Several studies have demonstrated the efficacy of TEAS in restoring upper limb function. This study aims to evaluate the impact of TEAS on upper limb motor recovery after stroke.ObjectivesThis study aims to evaluate the influence of TEAS on upper limb motor recovery after stroke and improve the quality of life in such patients.MethodsEight databases were systematically searched from inception to 1st October 2024. Two independent reviewers conducted the screening and data extraction of the study. The primary outcome measure was the Fugl Meyer Assessment of the Upper Extremity (FMA-UE), which evaluates upper extremity motor function in stroke patients. Secondary outcomes included the Modified Ashworth Scale (MAS) for assessing spasticity and the Modified Barthel Index (MBI) to evaluate patients’ abilities to perform activities of daily living. Data synthesis was conducted using RevMan 5.4 and Stata 14.0. The GRADE method was employed to assess the quality of evidence.ResultsA total of 16 trials involving 1,218 stroke patients were included in this meta-analysis. Meta-analysis showed that the TEAS significantly improved upper limb function (SMD = 1.70, 95CI% = 1.09 to 2.31, p < 0.00001, I2 = 93%; low certainty of evidence), reduced spasticity (SMD = −1.18, 95CI% = −1.79 to −0.58, p < 0.00001, I2 = 90%; very low certainty of evidence), and enhanced the ability to perform daily activities (SMD = 1.53, 95CI% = 0.85 to 2.20, p < 0.00001, I2 = 95%; low certainty of evidence).ConclusionOur results indicated that TEAS improved motor function and functional activities and reduced muscle tone in the upper limbs after stroke. However, these results should be interpreted with caution due to the limited strength of the evidence. High-quality, larger sample, multi-center studies are needed to validate these preliminary findings.Systematic review registrationThis study was registered on PROSPERO with registration number CRD42024592509. https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024592509